2011
DOI: 10.1002/jmri.22630
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of hypovascular hepatic nodules revealing no gadoxetic acid uptake in patients with chronic liver disease

Abstract: Purpose: To elucidate the natural history of hypovascular nodules that appear hypointense on hepatocyte-phase gadoxetic acid-enhanced MR images by focusing on hypervascularization over time. Materials and Methods:In this study, 135 hypovascular nodules revealing no gadoxetic acid uptake in 53 patients were examined. All nodules were retrospectively examined using serial follow-up computed tomography (CT) and MRI examinations until hypervascularity was observed on arterial-phase dynamic CT or gadoxetic acid-enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 31 publications
5
95
1
1
Order By: Relevance
“…80,81 If left untreated, more than 10z of these lesions will become hypervascular or conventional HCCs within a year. Among early HCCs identiˆed by gadoxetic acid-enhanced MR imaging, an especially important risk factor for hypervascularization is size exceeding 10 mm 87,88 (Fig. 9a-d).…”
Section: Room For Discussionmentioning
confidence: 99%
“…80,81 If left untreated, more than 10z of these lesions will become hypervascular or conventional HCCs within a year. Among early HCCs identiˆed by gadoxetic acid-enhanced MR imaging, an especially important risk factor for hypervascularization is size exceeding 10 mm 87,88 (Fig. 9a-d).…”
Section: Room For Discussionmentioning
confidence: 99%
“…28 Several recent studies have reported the hypervascularization of hypovascular nodules detected on gadoxetic acid-enhanced MR imaging. [17][18][19] Table 2 summarizes those study results and ours. One risk factor for hypervascularization is nodule size.…”
Section: Discussionmentioning
confidence: 79%
“…17 Because fatty changes in nodules are a characteristic histopathological feature of HGDN and early HCC 29,30 and a gradual decrease in OATP8 expression has been shown during multistep hepatocarcinogenesis, 27 it is reasonable to consider most hypovascular nodules with fat detected by gadoxetic acid-enhanced MR imaging to be HGDN or early HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now known that when such nodules follow their natural course, many eventually become hypervascular and progress to classical hypervascular HCC [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. For these reasons, it has recently become a reality in the diagnosis of early HCC that among existing imaging diagnostic modalities, EOB-MRI is achieving a level of diagnostic performance approaching that of liver pathology experts.…”
Section: Establishment Of the Concept Of Early Hccmentioning
confidence: 99%